Effect of beam shape and spatial energy distribution on weld bead geometry in conduction welding - Suder, Wojciech; Williams, Stewart W.; Ayoola, Wasiu A. (Elsevier, 2019)
The size of a projected beam onto a workpiece and its intensity distribution profile defines the response of the material to the applied laser heat. This means that not only the processing parameters, but also the optical set-up and process tools define the process and the resulting weld profile. In high power laser delivery systems the beam propagation characteristics of the laser beam can vary during processing. A change of the focal distance, for instance, alters the spot size projected on the workpiece as well as its intensity distribution. Some dynamic optical systems can also change the shape of the projected beam. Galvo-scanners induce a small distortion to the projected beam from circular to elliptical when the mirrors deflect the beam across the working domain. This continuous change of the spatial energy distribution may affect the process stability and material response locally. This work examines the influence of changing the shape of the projected beam and its energy distribution on the weld bead profile in conduction laser welding, which is also relevant to laser cladding and additive manufacture. It has been found that for the same optical set-up and system parameters, different bead profiles can be obtained with different degree of distortion of the beam profile. In addition, different intensity distribution profiles led to different penetration depths for the same nominal beam diameter and energy density due to the difference in peak intensity.
Keywords: Beam diameter; Conduction welds; Distortion of spot size; Weldbead profile geometry; Intensity distribution